Hubungan Gaya Komunikasi Guru Terhadap Motivasi dan Prestasi Siswa - Firdaus, Zayna; Sulistyani, Anjar; Arief, Achmad Abrory (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
This study aims to determine the relationship of teacher communication style to student’s motivation and learning achievement, as well as communication style that is often used by teachers in communicating with students. The method used by the author is a quantitative approach, with a sample of 10 teachers and 30 fifth grade students at SDN Ciapus 04 Bogor. The data collected in the study used a questionnaire, observation, and documentation. The data was processed using SPSS version 25 statistical analysis. The results showed that there was a relationship between teacher communication style and motivation and learning achievement of fifth grade students at SDN Ciapus 04 Bogor. It is said that the correlation is quite strong and the direction of the correlation is unidirectional. Communication style that is often used by teachers in communicating with fifth grade students is assertive communication style.Keywords: Communication Style, Motivation, Achievement